WAYS TO ACHIEVE HIGH EFFICIENCY WITH THE HELP OF DIGITAL TECHNOLOGIES IN THE AGRO-INDUSTRIAL COMPLEX - Ulugmurodov Farkhod Faxriddinovich; Maxmudov Javoxir Olimjonovich; Najmiddinov Shohruh Baxriddinovich; Egamkulov Davlatbek Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article touches on the topic of ways to achieve high efficiency using digital technologies in agro-industrial maimui and shows ways to achieve high efficiency using digital technologies and automation in agro-industrial maimui. This article describes modern technologies, such as 3D printing devices, robots, the Internet of Things, information systems and other digital services, and their application in the agro-industrial sector.